1996
DOI: 10.1111/j.1471-6712.1996.tb00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dinner Music on Food Intake and Symptoms Common in Dementia

Abstract: The influence of dinner music on food intake and symptoms common in dementia such as depressed mood, irritability and restlessness was studied. The study was carried out in a nursing-home ward in Sweden. Soothing music was played as dinner music for weeks, Swedish tunes form the 1920s and 1930s for two weeks and pop music for two weeks. Prior to these periods, there was one week without music, and at the end of the intervention there was a two-week control period. The effects of the intervention were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 19 publications
3
111
0
Order By: Relevance
“…This was also shown in a study by Ragneskog et al [15] focusing on eating while listening to music. Maybe the humming could be regarded as music to listen to.…”
Section: Reflections On the Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…This was also shown in a study by Ragneskog et al [15] focusing on eating while listening to music. Maybe the humming could be regarded as music to listen to.…”
Section: Reflections On the Resultssupporting
confidence: 74%
“…Music has been shown to have a positive influence on persons with dementia during music therapy and during music listening [13,14] , and during mealtime music listening has seemed to improve appetite [15] . Studies that have focused on morning care situations have shown that when the caregiver sings for or together with persons with dementia, so called Music Therapeutic caregiving [MTC] [16] , the persons with dementia appear relaxed [15,[17][18][19] , self-confident [17,18,20] , and are more active during the caring activity [19,21] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agitated behaviors responded better to individually tailored music than "classical relaxation music" (Gerdner, 2000) and aggression declined significantly when participants' preferred music was played during bath times (Thomas et al, 1997;Clark et al, 1998). "Off the shelf" music, by contrast, worked no better than hand massage (Remington et al, 2002), book readings (Groene, 1993) or mealtimes without music (Ragneskog et al, 1996). Tailoring music to individuals' preferences is clearly important.…”
Section: Treatmentsmentioning
confidence: 99%
“…Music (of the patient's preference) 124 reduced agitation, aggression, and mood disturbance under various conditions including eating and bathing. [125][126][127][128][129][130][131][132] One-on-one social interaction or videotapes of family members reduced verbally disruptive behaviors more than music. 127 However, there are conflicting preliminary reports of the benefits of using familiar audiotaped voices (simulated presence therapy) in improving mood, aggression, and agitation.…”
Section: Do Nonpharmacologic Interventions Other Than Education Impromentioning
confidence: 99%